Commercial limes (calcium hydroxide) in corn tortilla production: Changes in pH, color, sensory characteristics, and shelf life - Vazquez-Carrillo, María Gricelda; Palacios-Rojas, Natalia; Mier-Sainz Trapaga, Rafael; Garcia-Cruz, Leticia; Rosas-Zamora, Gabriela; Rosales-Nolasco, Aldo; Santillano-Gómez, Lizeth Carolina (Codon Publications, 2025)
Lime, an essential component of the nixtamalization process, influences several aspects of tortilla quality. This study evaluated the effect of six commercial limes of different purities on the quality of tortillas made from white and blue corn. The Ca(OH)(2) and heavy metal content in lime, color, pH, and calcium content in tortillas, acceptability by attributes, and shelf life were determined. Limes with lower levels of Ca(OH)(2) fell below the standard specifications and exceeded the limits for heavy metals such as arsenic (6.6 and 7.3 mg kg(-1)) and lead (2.4 mg > 21.6, blue > 5.7), calcium content (white > 200, blue > 176 mg 100 g(-1)), and lower luminosity. Moreover, these limes imparted better organoleptic characteristics to the tortillas, which led to a higher preference among the panelists. The purity of lime is a key factor in improving the quality and safety of the tortilla; thus, countries that adopt the nixtamalization process using lime should pay particular attention to the purity of the lime used in their processes, as it modifies the characteristics of the final product. In addition, manufacturers of food-grade lime must guarantee high purity to obtain a safe, high-quality food product.